ISLAMIC SOCIAL ENTREPRENEURSHIP IN REALIZING SOCIAL INCLUSION FOR PEOPLE WITH INTELLECTUAL DISABILITIES - Zahara, Jihan Nabila; Ryandono, Muhamad Nafik Hadi; Munifatussaidah, Asma (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: People with intellectual disabilities often face systemic barriers that limit their access to education, employment, and meaningful social participation. This study addresses the limited social and economic inclusion of people with intellectual disabilities, a group often marginalized and stigmatized in rural Indonesia. It examines how Islamic Social Entrepreneurship can serve as a model for empowerment to promote social inclusion in Karangpatihan Village, Ponorogo Regency. Methods: This research uses a qualitative explanatory case study; data were collected through interviews, observation, and documentation, and analyzed with pattern matching. Results: The findings reveal that Rumah Harapan Mulya’s empowerment program, through training in doormat and ciprat batik, integrates social entrepreneurship, business skills, and Islamic values “SAFTI” (Siddiq, Amanah, Fathanah, Tabligh, Istiqamah) in line with the maqasid al-Syariah (principles of Sharia). This integration enhances social recognition, participation, and economic contribution while reducing stigma against people with disabilities. Despite challenges in communication and financial management, the initiative successfully creates an inclusive and equitable environment. Conclusion and suggestion: Theoretically, this research contributes to the development of Islamic entrepreneurship studies by introducing Islamic Social Entrepreneurship as a sustainable and replicable empowerment framework. Practically, it offers insights for policymakers and social institutions on designing disability-inclusive empowerment programs.